Literature Review Pengaruh Asam Folat Pada Kadar Hemoglobin Untuk Wanita Prakonsepsi Dengan Anemia: Literature Review Effect of Folic Acid on Hemoglobin Levels for Preconceptional Women with Anemia - Putri Alifia Akhmad; Moneca Diah Listiyaningsih (Journal of Holistics and Health Sciences (JHHS), 2021)
Folic acid is important in the process of formation and maturation of erythrocytes, so that folic acid deficiency can manifest in anemia. Anemia is defined by hemoglobin levels in preconception women <12.0 g/dl, one of which is due to the lack of erythrocyte. Globally, the prevalence of anemia in women not pregnant (childbearing age) is 1.1%, and affects 19 million women not pregnant. Prevention of anemia in women of childbearing age can improve the degree of health of pregnant women, which ultimately contributes to a decrease in maternal and perinatal death. So that in preconception care is recommended anemia prevention measures in the form of nutritional interventions, one of which is recommended to prevent folic acid deficiency. The purpose of the study was to find out the influence of folic acid on hemoglobin levels of preconception women with anemia. literature review study, study 5 articles that meet inclusion and exclusion criteria. Search through Google Scholar, Garuda, and Pubmed, keywords that iron folic acid, folic acid, and anemia in preconception. from 5 articles examined there was an influence of folic acid on hemoglobin levels in preconception women. hemoglobin levels in preconception women are influenced by the adequacy of folic acid. So folic acid deficiency has an effect on the incidence of anemia in preconception women ABSTRAK Asam folat penting dalam proses pembentukan dan pematangan eritrosit, sehingga defisiensi asam folat bisa bermanifestasi pada anemia. Anemia didefinisikan dengan kadar hemoglobin pada wanita prakonsepsi <12,0 g/dl yang salah satunya dikarenakan kurangnya jumlah eritrosit. Secara global, prevalensi anemia pada wanita tidak hamil (usia subur) yaitu 1,1%, dan mempengaruhi 19 juta wanita tidak hamil. Pencegahan anemia pada wanita usia subur dapat meningkatkan derajat kesehatan wanita hamil, yang pada akhirnya berkontribusi pada penurunan kematian ibu dan perinatal. Sehingga dalam pelayanan kesehatan prakonsepsi (preconception care) dianjurkan tindakan pencegahan anemia berupa intervensi gizi yang salah satunya dianjurkan untuk mencegah defisiensi asam folat. Tujuan penelitian untuk mengetahui pengaruh asam folat pada kadar hemoglobin wanita prakonsepsi dengan anemia. Studi literature review, menelaah 5 artikel yang memenuhi kriteria inklusi dan eksklusi. Pencarian melalui Google Scholar, Garuda, dan Pubmed, kata kunci yang iron folic acid, asam folat, dan anemia in preconception. Dari 5 artikel yang ditelaah didapatkan adanya pengaruh asam folat terhadap kadar hemoglobin pada wanita prakonsepsi. Kadar hemoglobin pada wanita prakonsepsi salah satunya dipengaruhi oleh tingkat kecukupan asam folat. Sehingga defisiensi asam folat berpengaruh pada kejadian anemia pada wanita prakonsepsi.